Penerapan E-Book Daging untuk Meningkatkan Hasil Belajar Siswa di SMK Negeri 8 Surabaya - Kingkin Via Febrina; Lucia Tri Pangesthi; Sri Handajani; Ita Fatkhur Romadhoni (Journal Innovation In Education, 2025)
This study aims to determine (1) the learning outcomes through the implementation of an e-book on meat material at SMK Negeri 8 Surabaya, and (2) student responses to the implementation of the e-book on meat material at SMK Negeri 8 Surabaya. The research method used is the pre-experiment method, where students were provided with an e-book as a learning resource. Pre-tests and post-tests were conducted to measure the improvement in students' learning outcomes after using the e-book. The subject of this study is the e-book containing meat-related material, designed to make it easier for students to understand the topic being taught. The research instruments used include a test sheet to measure students' learning outcomes and a questionnaire to gather student responses to the e-book implementation. Data analysis was conducted using a quantitative approach, where the data collected was in numerical form and analyzed statistically. This aimed to determine whether the use of the meat-related e-book had a significant impact on students' learning outcomes. The results of the study showed that in the cognitive domain, there was an improvement in learning outcomes by 51.94%, but this improvement was categorized as less effective. This indicates that while the e-book contributed to the learning process, its impact on students' learning outcomes was still limited. Factors that may affect the effectiveness of the e-book implementation could be related to the quality of the content, delivery method, or other limitations that influence students' understanding. On the other hand, student responses to the implementation of the e-book on meat material showed positive results, with an average response score of 84%, which is categorized as very good. This indicates that students responded to the e-book implementation enthusiastically and positively. Although the learning outcomes were not optimal, the implementation of the e-book can be considered a good alternative in learning, with improvements that could enhance its effectiveness.